A comparative study of dry-coated fumed metal oxides for enhanced cycling performance of SiOx/C anodes in lithium-ion batteries - Ana L. Azevedo Costa; Mareike Liebertseder; Tatiana Gambaryan-Roisman; Daniel Esken; Frank Menzel (Electrochemistry Communications)
Silicon (Si) is a promising anode material for next-generation lithium-ion batteries (LIBs) due to its high theoretical capacity. However, its practical application is hindered by significant volume changes during cycling, leading to particle pulverization, loss of electrical contact, and rapid capacity fading. To address these challenges, we study the effect of dry particle coating with nanostructured fumed metal oxides (TiO2, MgO, ZrO2, and Al2O3) on enhancing the electrochemical performance of SiOx/C anodes. The dry coating process, a facile and scalable technique, effectively attaches the metal oxide nanoparticles onto the SiOx/C surface, forming a protective layer. The coated anode active materials (AAMs) exhibit improved cycling stability and rate capability compared to the uncoated SiOx/C, with the Al2O3-coated anode demonstrating the most promising overall performance. The effective and uniform distribution of the porous coating acts as a protective layer, reducing side reactions while simultaneously enhancing ion diffusion kinetics and improving electrolyte accessibility. Detailed characterization reveals that the Al2O3 coating promotes the controlled formation of a LiF-rich solid electrolyte interphase (SEI) layer, contributing to enhanced ionic conductivity and stability. This study highlights the potential of dry particle coating with different metal oxides as a promising strategy for developing high-performance Si-based anodes for next-generation LIBs.